2018
DOI: 10.1093/jrr/rry050
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial–mesenchymal transition in non-targeted lung tissues of Kunming mice exposed to X-rays is suppressed by celecoxib

Abstract: Lung cancer is one of the highest health risks caused by ionizing radiation, which induces both direct effects and non-targeted effects. However, whether radiation-induced non-targeted effects result in epithelial–mesenchymal transition, a critical process during tumorigenesis, in non-targeted lung tissues remains unknown. In the present study, Kunming mice were subjected to whole-body, cranial or local abdominal irradiation of single-dose or fractionated 4 Gy X-rays, and the expressions of epithelial–mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…NSAIDs are non-hormonal compounds that are commonly used as symptomatic treatment for dysmenorrhea and heavy bleeding associated with adenomyosis (10,11). Findings from recent studies have suggested that NSAIDs are also capable of inhibiting angiogenesis, proliferation, the expression of aromatase P450 and epithelial-mesenchymal transition (EMT) in numerous cancer models, such as colorectal cancer, prostate cancer and human glioblastoma endothelial cells, highlighting their potentially novel properties (12)(13)(14). Additionally, the long-term use of NSAIDs has been proposed as a therapeutic Celecoxib, a selective COX-2 inhibitor, markedly reduced the severity of tamoxifen-induced adenomyosis in a murine model strategy for a number of malignancies, including prostate, colon and breast cancer (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…NSAIDs are non-hormonal compounds that are commonly used as symptomatic treatment for dysmenorrhea and heavy bleeding associated with adenomyosis (10,11). Findings from recent studies have suggested that NSAIDs are also capable of inhibiting angiogenesis, proliferation, the expression of aromatase P450 and epithelial-mesenchymal transition (EMT) in numerous cancer models, such as colorectal cancer, prostate cancer and human glioblastoma endothelial cells, highlighting their potentially novel properties (12)(13)(14). Additionally, the long-term use of NSAIDs has been proposed as a therapeutic Celecoxib, a selective COX-2 inhibitor, markedly reduced the severity of tamoxifen-induced adenomyosis in a murine model strategy for a number of malignancies, including prostate, colon and breast cancer (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is an important process to transform epithelial cells into mesenchymal cells, which is involved in tumorigenesis, invasion and metastasis [ 44 , 45 ]. In the process of EMT, the epithelial marker E-cadherin is downregulated, while the mesenchymal markers N-cadherin, fibronectin, and vimentin are upregulated significantly [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is an important process to transform epithelial cells into mesenchymal cells, which is involved in tumorigenesis, invasion and metastasis [42,43]. In the process of EMT, the epithelial marker E-cadherin is downregulated, while the mesenchymal markers N-cadherin, bronectin, and vimentin are upregulated signi cantly [44].…”
Section: Mechanistic Study On Therapeutic Effectmentioning
confidence: 99%